CONTEMPORARY UNDERSTANDING AND FUNCTIONALITY OF BELIEF: THE CASE OF VIĻAKA - Šuplinska, Ilga (Via Latgalica, 2016)
Students of the philology program at Rēzekne Higher Education Institution have been participating in field research since 2002. The subject of field research conducted in Viļaka – folk belief and superstition – was not chosen by chance. While conducting an expedition, information was received that Viļaka has several natural observers who study and record beliefs; however, during the period of field research only Vilis Bukšs, one of Latvia’s most famous naturalists, agreed to share his experiences. 58 respondents were surveyed in Viļaka, and 130 beliefs were recorded between 19 respondent interviews. Linguoculturological and linguocognitological analysis principles were used in the research (Wierzbicka 1997, Krasnikh 2003, Maslova 2004, Sabimova 2013, Fattakhova, Kulkova 2015). As previously mentioned, the empirical material consists of Bukšs’ catalogue of beliefs (529 units), in addition to those collected in Viļaka (~130 units), illustrating comprehension on the part of the respondents of contemporary genres of belief.The article is divided into two main sections: the genres and functions of beliefs, and Bukšs’ calendar of beliefs and language profile.Contemporary belief is studied from the perspective of genre as well as language. There are various definitions that describe the genre of belief. In this article – belief is a genre of short folklore that influences human behavior, and which is primarily implicated in connection with natural phenomena, the qualities of objects and life events.Estrangement from nature, trust in various sources of information and the negative, skeptical attitude of the church frames belief as meteorological, minimizing discourse of its ability to explain regularities in life; however, at the same time real superstitious beliefs are still clearly visible – premonitions associated with visceral reactions, vegetable planting, growth observations, etc., and the discourse of belief is certainly present for the people of Viļaka. In general, however, superstitions have lost their regulative and informative functions, and the prognostic function is more associated with a desire for peace of mind, rather than reliance upon self-evident assumptions to forecast the future.Bukšs’ natural observation calendar shows that belief today is of fundamental importance to the world order, natural processes and the modeling and interpretation of human behavior.